Guidance behind criticisms: the good parenting as portrayed in the first Malay autobiography - Hamdan, Rahimah; Sujud, Arba'ie (Canadian Center of Science and Education, 2019)
This paper was aimed at identifying the guidance to parenting that emerged in the first Malay autobiography, the Hikayat Abdullah, and subsequently, to analyse those instructions on parenting in the context of the traditional Malay society of the 19th century. The recognition accorded to Abdullah Munshi as the Father of Modern Malay Literature has attracted various reactions from scholars. Some scholars regard Abdullah Munshi as the one who brought renewal to Malay literature through his courageous criticism of the customs and culture that had been in practice for generations. On the other hand, there are scholars who disapprove of that recognition being given to him and who consider Abdullah Munshi’s criticisms in his works as a deviation from the reality expressed in previous works. Nevertheless, not a single study has suggested that perhaps Abdullah Munshi firmly emphasized those criticisms with the intention of providing some sort of guidance. Hence, by analysing certain texts in the Hikayat Abdullah and by reviewing the evidence from the perspective of Swettenham (1895), who objectively evaluated the thinking and culture of the Malay community, this study was able to rectify the image of Abdullah Munshi, who, all this while, was considered to be pro-British because of his harsh criticism of the Malay community. Moreover, those criticisms were meant to provide guidance for the family institution, especially for parents. This indirectly proves that Abdullah Munshi took a serious view of parenting and believed that improvements were necessary to produce a dignified and civilized generation. In conclusion, the autobiography, the Hikayat Abdullah, was not just a new form of writing that deviated from the conventions of traditional Malay literature, but was the fruit of the wisdom of the author that was meant to benefit his readers.